Effect of hydroxypropyl-methyl cellulose ether on rheology of cement paste plasticized by polycarboxylate superplasticizer. (30th January 2018) - Ma, Baoguo; Peng, Yi; Tan, Hongbo; Jian, Shouwei; Zhi, Zhenzhen; Guo, Yulin; Qi, Huahui; Zhang, Ting; He, Xingyang
Highlights: Agglomeration and even precipitation of HPMC in pore solution would take place. HPMC with greater molecular weight is more easily agglomerated in pore solution. Negative effect of HPMC on dispersion of PCE was confirmed. HPMC with greater molecular weight results in stronger negative effect. Abstract: Generally, bleeding and segregation can be solved with addition of hydroxypropyl-methyl cellulose ether (HPMC) in real concrete. However, the negative effect of this on dispersion of polycarboxylate superplasticizer (PCE) can always be found. In order to deeply understand this negative effect, the rheology of cement paste in the presence of PCE and HPMC was investigated, and the mechanism behind the interaction between PCE and HPMC was revealed with total organic carbon analyzer, X-ray photoelectron spectrometer and dynamic light scattering. The results show that addition of HPMC can obviously increase the plastic viscosity and yield stress of cement paste plasticized by PCE, showing negative effect on fluidity. One reason for this negative effect is that HPMC can be combined with Ca 2+ in pore solution, resulting in agglomeration and even precipitation, which can consume and invalid PCE; another reason is that HPMC can perturb the adsorption of PCE to exert dispersion by competitive adsorption. By contrast, much stronger negative effect can be observed with greater molecular weight of HPMC. It is inferred that proper molecular weight of HPMC can balance the negative effect of HPMC on dispersion of PCE and the viscosity-enhancing effect of HPMC to improve bleeding and segregation. Such results were expected to provide guidance on the use of HPMC to optimize workability of cement-based materials plasticized by PCE in real engineering practice.